2020
DOI: 10.1007/s11837-020-04510-z
|View full text |Cite
|
Sign up to set email alerts
|

Effective Recovery Process of Copper from Waste Printed Circuit Boards Utilizing Recycling of Leachate

Abstract: This study presents an optimized leaching and electrowinning process for the recovery of copper from waste printed circuit boards including studies of chemical consumption and recirculation of leachate. Optimization of leaching was performed using response surface methodology in diluted sulfuric acid and hydrogen peroxide media. Optimum leaching conditions for copper were found by using 3.6 mol L−1 sulfuric acid, 6 vol.% hydrogen peroxide, pulp density of 75 g L−1 with 186 min leaching time at 20°C resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…PCBs were crushed into 1 × 1 cm pieces with pliers and treated with an aq 5 M HNO 3 solution at 70 °C to prepare a stock solution, which was used for the preparation of catalytic materials. Nitric acid has been reported for metal leaching of E-waste. Inductively coupled plasma mass spectrometry (ICP-MS) analysis of the acid leachate stock solution showed that copper was the main component (∼40 g/L), with significant amounts of Ni (1.33 g/L). Other metals such as Zn, Fe, Pb, and Sn have been detected in much smaller quantities (<1 g/L).…”
Section: Resultsmentioning
confidence: 99%
“…PCBs were crushed into 1 × 1 cm pieces with pliers and treated with an aq 5 M HNO 3 solution at 70 °C to prepare a stock solution, which was used for the preparation of catalytic materials. Nitric acid has been reported for metal leaching of E-waste. Inductively coupled plasma mass spectrometry (ICP-MS) analysis of the acid leachate stock solution showed that copper was the main component (∼40 g/L), with significant amounts of Ni (1.33 g/L). Other metals such as Zn, Fe, Pb, and Sn have been detected in much smaller quantities (<1 g/L).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a similar investigation was conducted by [33], which focused mainly on copper leaching and was followed by electro-winning process (Figure 1b). In contrast to the earlier study, mentioned in the above paragraph, here the authors used sulfuric acid (H 2 SO 4 ) in the presence of H 2 O 2 as an oxidant.…”
Section: Chemical Leachingmentioning
confidence: 95%
“…As part of extractive metallurgy, hydrometallurgy is a well-established process which is applied successfully for metal leaching from both primary and secondary resources [22,26]. Nowadays, several researches are being undertaken on chemical leaching of critical metals including REE [26][27][28][29], base metals [30][31][32][33] and precious metals [34][35][36] from e-waste materials. The process is mainly divided into three steps (leaching, solid liquid separation/purification and metal recovery).…”
Section: Chemical Leachingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that Jiangsu Province, as one of the most crucial electronic products manufacturing areas in China, produces more than 350,000 tons of spent coppery etchant every year [3]. Spent coppery etchant is a kind of hazardous waste (HW22) listed on the National Hazardous Waste List and usually contains about 10% copper and other heavy metals in varying amounts, such as zinc, nickel, cadmium, chromium, and arsenic [4].…”
Section: Introductionmentioning
confidence: 99%